Continuous Leakage-Amplified Public-Key Encryption With CCA Security. (21st April 2021) - Zhang, Wenzheng; Qiao, Zirui; Yang, Bo; Zhou, Yanwei; Zhang, Mingwu
Abstract: Secret key leakage has become a security threat in computer systems, and it is crucial that cryptographic schemes should resist various leakage attacks, including the continuous leakage attacks. In the literature, some research progresses have been made in designing leakage resistant cryptographic primitives, but there are still some remaining issues unsolved, e.g. the upper bound of the permitted leakage is fixed. In actual applications, the leakage requirements may vary; thus, the leakage parameter with fixed size is not sufficient against various leakage attacks. In this paper, we introduce some novel idea of designing a continuous leakage-amplified public-key encryption scheme with security against chosen-ciphertext attacks. In our construction, the leakage parameter can have an arbitrary length, i.e. the length of the permitted leakage can be flexibly adjusted according to the specific leakage requirements. The security of our proposed scheme is formally proved based on the classic decisional Diffie–Hellman assumption.